1988
DOI: 10.1149/1.2096041
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Titanium Silicide Formation on Dopant Redistribution

Abstract: This paper reports on boron and arsenic redistribution during the TiSi2 self-aligned silicide process as applied to shallow (<0.2 ~tm) junctions. Dopant loss was seen to occur through evaporation from the silicide surface, segregation into the Ti-rich outer layer which is subsequently removed, and diffusion into the silicide layer. Depending on the silicide and junction annealing temperatures, up to 99% of the implanted dopant dose can be lost via these three mechanisms. Dopant loss is particularly acute when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 30 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…Whether or not Ti silicidation at low temperature leads to different P redistribution at the TiSi x /n + -Si interface is inspected by secondary ion mass spectroscopy (SIMS), as displayed in figure 11. It is revealed that a portion of P atoms diffuse into the ultrathin TiSi x , and no accumulation of P at the TiSi x /n + -Si interface is evident for both the reference and the sample with Ge PAI, due to higher diffusivity of P in TiSi x than that in Si [68][69][70]. It is worth noting that with Ge PAI, the out-diffusion of P atoms is aggravated since a strong intermixing between Ti and Si is revealed.…”
Section: Ti Silicidation With Ge Paimentioning
confidence: 89%
“…Whether or not Ti silicidation at low temperature leads to different P redistribution at the TiSi x /n + -Si interface is inspected by secondary ion mass spectroscopy (SIMS), as displayed in figure 11. It is revealed that a portion of P atoms diffuse into the ultrathin TiSi x , and no accumulation of P at the TiSi x /n + -Si interface is evident for both the reference and the sample with Ge PAI, due to higher diffusivity of P in TiSi x than that in Si [68][69][70]. It is worth noting that with Ge PAI, the out-diffusion of P atoms is aggravated since a strong intermixing between Ti and Si is revealed.…”
Section: Ti Silicidation With Ge Paimentioning
confidence: 89%
“…The redistribution of dopant within the silicide presents two more fundamental issues; the extensive loss of dopant via evaporation, which can often amount to 90% of the implanted dose (10), and the diffusion of dopant within the silicide. Dopant diffusion in silicides can be divided into two groups; those with very slow bulk diffusion, where only grain boundary diffusion plays a role, and those where the bulk diffusion is rapid enough so that dopant can distribute more or less homogeneously throughout the grains in the films.…”
Section: Resultsmentioning
confidence: 99%
“…9, demonstrating the effect of slow As diffusion through the silicide. If diffusion through the silicide becomes rate limiting, the evaporation rate should be determined by the diffusional flux which can be written as F = D-- [10] CoSi2, which is far more than the amount evaporated. Thus, it is believed that the diffusion of boron in CoSi2 is not the rate limiting step of the dopant loss process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations